Andragogical Perspectives in Designing Digital Games for Older Adults: Maximizing Interaction and Experience - Nurul Farinah, Mohsin (-, 2023)
The revolution of digital games has been advancing years by years. Digital games no longer serve just as entertainment but can potentially be used in different areas, such as the healthcare industry. The worldwide population of older adults is increasing, leading to an ageing world. The advancement of digital game technology can help to facilitate this ageing population. However, the current commercialised digital games are not designed and developed based on older adults’ limitations. In addition, there is limited of guideline on designing and developing games specifically for older adults that consider andragogy principles. Therefore, this study proposes the Purpose, Design, Play and Experience guideline as a guideline for designing and developing digital games for older adults by reflecting the key principles of andragogy. In this study, an application named Otak Me! has been developed based on the guideline in the proposed guideline and tested by the target group, the older adults in Malaysia aged 55 and above. Participants’ gaming experiences and user interface satisfaction were measured using Game Experience Questionnaire (GEQ) and Questionnaire for User Interface Satisfaction (QUIS). Based on the finding, Otak Me! received positive feedback where the positive items include the participants’ feeling toward the Otak Me! application have the highest mean score compared to other items in GEQ with a score 4.00 from the participants, which vastly helped evaluate and validate the game design for older adults. Therefore, by playing and engaging with games in the Otak Me! application give benefit towards the older population in term of enjoyment.